“Show of the heart” volunteer recruitment and retention campaign. - Leung, Ka Yun. (2011)
Show of the Heart (SOTH) is a grounds-up initiative to create an effective and influential grassroots network amongst youth and young adult volunteers, with the ultimate goal of encouraging committed volunteers. Based on the literature and formative research, we defined a committed volunteer as one who is both selfless and willing to give of his or her time on a regular basis of at least one to two occasions a month.We crafted a volunteer recruitment and retention campaign by adapting Bussell and